2020
DOI: 10.2147/hmer.s263840
|View full text |Cite
|
Sign up to set email alerts
|

<p>Repurposing of N-Acetylcysteine for the Treatment of Dengue Virus-Induced Acute Liver Failure</p>

Abstract: The prevalence of dengue infection-induced acute liver damage is increasing from time to time. Since it has no specific antiviral treatment in the world, people in endemic areas suffer more from dengue disorders. Thus, there is a need for searching options for the treatment of dengue-induced acute liver failure. N-acetylcysteine, which is used for the treatment of nasal congestion disorder and paracetamol overdose toxicity, could be used as a definitive therapy for dengue virus-induced acute liver disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…La FHA por dengue no tiene un tratamiento específico, sin embargo, dentro del ejercicio terapéutico conviene identificar aquellos pacientes con enfermedad hepática crónica, excluir enfermedades hepatobiliares tratables o emergentes, considerar el riesgo individual de pacientes con condiciones específicas como los diabéticos y excluir etiologías como la lesión hepática inducida por fármacos (DILI), debido a que son grupos de riesgo (16). El uso de N-acetil-cisteína por su actividad antioxidante, ha sido descrito en múltiples reportes de casos generalmente con buenos resultados cuando se usa de manera temprana en pacientes con encefalopatía hepática por DENV (17). El uso actual de sistemas no biológicos como el de recirculación molecular adsorbente (MARS, por sus siglas en ingles), se ha practicado con seguridad en FHA de diferentes etiologías, mostrando beneficios sobre la ictericia, la inestabilidad hemodinámica, la hipertensión portal y endocraneana, y la encefalopatía hepática con reportes favorables en la FHA por dengue (18).…”
Section: Discussionunclassified
“…La FHA por dengue no tiene un tratamiento específico, sin embargo, dentro del ejercicio terapéutico conviene identificar aquellos pacientes con enfermedad hepática crónica, excluir enfermedades hepatobiliares tratables o emergentes, considerar el riesgo individual de pacientes con condiciones específicas como los diabéticos y excluir etiologías como la lesión hepática inducida por fármacos (DILI), debido a que son grupos de riesgo (16). El uso de N-acetil-cisteína por su actividad antioxidante, ha sido descrito en múltiples reportes de casos generalmente con buenos resultados cuando se usa de manera temprana en pacientes con encefalopatía hepática por DENV (17). El uso actual de sistemas no biológicos como el de recirculación molecular adsorbente (MARS, por sus siglas en ingles), se ha practicado con seguridad en FHA de diferentes etiologías, mostrando beneficios sobre la ictericia, la inestabilidad hemodinámica, la hipertensión portal y endocraneana, y la encefalopatía hepática con reportes favorables en la FHA por dengue (18).…”
Section: Discussionunclassified
“…NAC can also reduce dengue virus infectivity during admission, replication, post-translation, RNA synthesis, and exocytosis. 6, 16 In a retrospective analysis, the dose of NAC given was intravenously 100 mg/kg/day for 5 days, followed by 12.5 mg/day. kgBW/hour for 4 hours followed by 6.25 mg/kgBW/hour for 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Management of ALF in dengue infection is largely supportive in an intensive care setting. Some of the centers have used NAC in adults with variable results but it is not part of our management protocol and its use was sporadic (21,22). We did not find any significant difference in survival with the use of NAC though Sriphongphankul et al (16) from Thailand found it to be beneficial in dengue PALF.…”
Section: Discussionmentioning
confidence: 99%